2010
DOI: 10.3810/pgm.2010.09.2199
|View full text |Cite
|
Sign up to set email alerts
|

The Single-Dose Pharmacokinetics of NWP06, a Novel Extended-Release Methylphenidate Oral Suspension

Abstract: A single dose of 60 mg NWP06 is equally bioavailable to two 30-mg doses of IR MPH. NWP06 has a lower peak concentration than IR MPH. Both study treatments were well tolerated, as all AEs were rated as mild in this healthy adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…However, the difference in C max between fed and fasted conditions was small (geometric mean ratio 127.6% [90%CI, 119.9% to 135.8%]). In an open‐label, randomized crossover study, the C max for MEROS 60 mg administered in a fasted state was substantially lower (geometric mean ratio 69.13% [90%Cl, 63.72% to 75.00%]) compared with an equivalent dose of an immediate‐release MPH oral solution (30 mg twice daily); thus, the increased C max observed when MEROS was administered after a high‐fat, high‐calorie meal was lower than that observed with an equivalent dose of the reference treatment, fasted. Further, the 90%CIs for the AUC 0–t and AUC 0–inf geometric mean ratios fell within the standard 80% to 125% bioequivalence acceptance range, indicating no food effect on the overall (rate and extent) exposure in these healthy adult subjects.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, the difference in C max between fed and fasted conditions was small (geometric mean ratio 127.6% [90%CI, 119.9% to 135.8%]). In an open‐label, randomized crossover study, the C max for MEROS 60 mg administered in a fasted state was substantially lower (geometric mean ratio 69.13% [90%Cl, 63.72% to 75.00%]) compared with an equivalent dose of an immediate‐release MPH oral solution (30 mg twice daily); thus, the increased C max observed when MEROS was administered after a high‐fat, high‐calorie meal was lower than that observed with an equivalent dose of the reference treatment, fasted. Further, the 90%CIs for the AUC 0–t and AUC 0–inf geometric mean ratios fell within the standard 80% to 125% bioequivalence acceptance range, indicating no food effect on the overall (rate and extent) exposure in these healthy adult subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, MEROS administered as a single oral dose of 60 mg (12 mL oral suspension equivalent to 25 mg methylphenidate HCl per 5 mL [5 mg/mL]) demonstrated a favorable safety profile in healthy adult subjects under fasting and fed conditions. The AEs reported during the study were anticipated and are common among the AEs reported following administration of methylphenidate …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This new formulation can potentially fill a void in stimulant preparations, especially useful for children not able to swallow pills who also may not be suitable for a transdermal administration of medications. A single-dose pharmacokinetics study of methylphenidate hydrochloride in 14 children (aged 9-15 years) concluded that the pharmacokinetics of methylphenidate hydrochloride was linear and dose proportional and that there were no age-related pharmacokinetic differences (Childress & Berry, 2010). The study, though focused on singledose pharmacokinetics and limited to a small sample size, demonstrated that methylphenidate hydrochloride had a pharmacokinetic profile similar to other extended-release preparations and was safe and well tolerated by children aged 9-15 years with ADHD.…”
Section: Newer Stimulant Formulationsmentioning
confidence: 99%